Utility of Orthodontic Braces as Flexible Splint for Stabilizing an Avulsed Tooth: A Case Report - J. Leidenz; Sarah C. Soto Perez (Case Reports in Dentistry)
Dental avulsion is a traumatic dental injury with complete displacement of the tooth outside the bony socket. Both primary and permanent teeth are predisposed to such traumatic incidents. The most effective treatment in such cases is tooth replantation. Additionally, a short-term flexible splint is needed to stabilize the avulsed/replanted tooth. This case report describes orthodontic braces as a standardized flexible splint option for the treatment of tooth avulsion. Herein, the case of a 9-year-old female patient who presented to a private dental clinic with an avulsed upper left central incisor, 1 h after the accident has occurred. Once the tooth was replanted with all the necessary precautions, orthodontic braces and wire were utilized to stabilize the tooth. Most dental splints are custom-made, requiring thorough professional knowledge and expertise for their fabrication and placement. The protocol described in this report is aimed at easing tooth stabilization using materials within the scope of a basic dental setup consultation room.